Proporsi Konsumsi Rumah Tangga Pembudidaya Ikan Patin (Pangasius sp.) di Kecamatan Talang Kelapa Kabupaten Banyuasin - Lia Perwita Sari; Rih Laksmi Utpalasari (Universitas Sriwijaya, 2020)
The purpose of this study was to determine the characteristics and comparison of the level of household food consumption of catfish (Pangasius sp.) farmer’s in Talang Kelapa District. Determination of the location was done intentionally (purposive). The research sample was taken using the accidental sampling method. There are 17 groups of consumption catfish farmers at Talang Kelapa District while only 7 groups focus on catfish culture with a total of 82 people so the sample is 20 people. The data used include primary data and secondary data. Data were analyzed descriptively qualitative and quantitative descriptive. Researchers used qualitative methods by analyzing the characteristics of each respondent. The proportion of household consumption of catfish farmers was analyzed using tabulation. The results showed that respondents aged between 29-52 years, had an average number of family members of 3 people and the highest level of education at the elementary school level. The household consumption pattern of Catfish Farmers (Pangasius sp.) at Talang Kelapa District are dominated by non-food consumption which is Rp.2,851,000/month while food consumption is only Rp.987,361.11. This is indicated by the percentage of food consumption by 25.73% and non-food consumption by 74.27%.